Evaluating Certified Indonesian EFL Teachers’ Performance: A Case Study in a High School in Aceh - Zulfikar Zulfikar (Universitas Negeri Makassar, 2021)
This study is entitled “Evaluating Certified Indonesian EFL Teachers’ Performance: A Case Study in a High School in Aceh”. The objective of this study is to identify to what extent Indonesia’s teacher certification program affects English as a Foreign Language (EFL) teachers’ instructional performance. The data were collected through in-depth interview and observations in a prominent state senior high school in Aceh Besar, Aceh, involving three certificated EFL teachers, fifteen EFL learners and the vice principal of curriculum affairs as participants. The data were subsequently analyzed by thematic analysis with the results distributed into separate themes. The results showed that even though all the teachers were knowledgably well-versed in their ability to devise well-elaborated lesson plans, two of them still exhibited a relatively strict adherence to the whole-class and teacher-centered instructions, with limited use of medias and varied learning sources, causing concern for both EFL learners and the school’s vice principal of curriculum affairs.